Percutaneous Techniques, Limitations and Challenges for the Failed Surgical Mitral Intervention. (March 2019) - Nyman, Charles B.; Shook, Douglas C.; Shernan, Stanton
The advent of percutaneous therapies has significantly altered therapeutic options for patients with valvular heart disease. Building on the success of transcatheter aortic valve replacement, both expanded indications and purpose-built devices are now being used to address percutaneous approaches for mitral valve pathology. While surgical mitral valve repair remains the gold standard for addressing significant mitral valve pathology, there has been a progressive increase in the utilization of bioprosthetic valves despite their limited lifespan. The risks of reoperation to address mitral valve repair failure or bioprosthetic valve dysfunction is not insignificant. In light of the aging population and the potential for significant associated comorbidities, less invasive alternative techniques hold particular appeal. Utilization of commercially available transcatheter aortic valve replacement valves for failed surgical valves has been shown to have better short-term mortality than would be predicted for open reoperation. As a result, the US Food and Drug Administration approved the utilization of transcatheter mitral valve-in-valve replacement for the failed bioprosthetic valve in high surgical risk patients. Despite the favorable outcomes, transcatheter mitral valve-in-valve is not without procedural challenges and potential complications including malpositioning, embolization, paravalvular leak, and outflow tract obstruction. Awareness of these challenges, mitigation strategies, and therapeutic options is imperative to optimizing outcomes in this high-risk patient population.